Kajian Hipersemiotika Terhaap Liwah dan Rayah Sebagai Identitas Organisasi HTI - P. Tumewu, Noufal; Alfan Shidqon; Zakiyan Rifqa (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
As an organization that seeks a caliphate government, Hizbut Tahrir has a number of symbols that characterize it. One symbol that is strongly attached to Hizbut Tahrir's identity is the liwa and rayah flag. This flag is often an integral part of various activities and demonstrations carried out by this organization, so that it creates an understanding among the public that the flag with the shahada written in it is the official identity of Hizbut Tahrir. in order to examine the understanding of the community related to the liwa and rayah flags, this research uses a leatherative method with a hypersemiotic approach as proposed by Umberto Eco. Through this approach, this paper aims to understand how hypersemiotic forms are formed in people's thinking related to the symbolism of this flag. although the Hizbut Tahrir group explicitly considers that the liwa and rayah are Islamic flags, the practices of their activities always involve these flags which have created an understanding among the public that the flag is a symbol of Hizbut Tahrir. This phenomenon gives rise to various forms of hypersemiotics, including the recyle sign that reflects the rejection of Hizbut Tahrir in several countries, with the liwa and rayah flags in it. In addition, there is also an extreme sign (superlative sign) that shows how this organization is considered dangerous while the liwa and rayah flags remain a strong symbol of identity for them. Thus, people's understanding and interpretation of the liwa and rayah flags produce various forms of hypersemiotics that reflect the complexity of identity and perceptions of Hizbut Tahrir.